Understanding Human Nature from Quranic Perspective - Anwar Sutoyo; Ulya Mahmudah; Abu Yazid Abu Bakar (Indonesian Journal Of Educational Research and Review, 2022)
The understanding of human nature is very important for human resource development, because that understanding will be a starting point in establishing development objectives, development strategies, method selection, and the types of media used. The main problem that has arisen so far is that the understanding of human nature is only based on the results of quantitative research, without considering the information from the Essence of the Supreme Creator of human (revelation), and consequently there are missing elements which limit the development of human resources. The quantitative studies only discuss things relating to physical, psychological, and social aspects; while important things such as the human creation process and its purpose, humanity's status before God, its potential and its development have not received enough attention. To find answers to the above shortcomings, this qualitative research utilizing document analysis technique of the Quran main verses relating to humanity was conducted using maudhu‘i interpretation method, namely by studying verses which are related to humanity through the understanding of the interpreters of the Quran. For the triangulation purposes, references were also made to the Hadiths – the words of Prophet Muhammad – as well as books of Tafsir, the translated versions of the Quran in local language. The aspects of human creation, the purpose of creation, and potentials and weaknesses of mankind were discussed in details by the researchers.